Identification of spatial and topographical metrics for micro hydropower applications in irrigation infrastructure - Campbell, Brian, author; Grigg, Neil, advisor; Catton, Kimberly, advisor; Zimmerle, Dan, committee member (Colorado State University. Libraries, 2012)
A recent agreement between the Federal Energy Regulatory Commission and the State of Colorado seeks to streamline regulatory review of small, low-head hydropower (micro hydropower) projects located in constrained waterways, (Governor's Energy Office, 2010). This regulatory change will likely encourage the development of micro hydropower projects, primarily as upgrades to existing infrastructure. Previous studies of low-head hydropower projects have estimated the combined capacity of micro hydro projects in Colorado between 664 MW to 5,003 MW (Connor, A.M., et al. 1998; Hall, D.G., et al. 2004, 2006). However, these studies did not include existing hydraulic structures in irrigation canals as possible hydropower sites. A Colorado Department of Agriculture study (Applegate Group, 2011) identified existing infrastructure categories for low head hydropower development in irrigation systems, which included diversion structures, line chutes, vertical drops, pipelines, check structures and reservoir outlets. However, an accurate assessment of hydropower capacity from existing infrastructures could not be determined due to low survey responses from irrigation water districts. The current study represents the first step in a comprehensive field study to quantify the type and quantity of irrigation infrastructure for potential upgrade to support micro hydropower production. Field surveys were conducted at approximately 230 sites in 6 of Colorado's 7 hydrographic divisions at existing hydraulic control structures. The United States Bureau of Reclamation contributed approximately 330 additional sample sites from the 17 western states. The work presented here describes a novel method of identifying geospatial metrics to support an estimation of total site count and resource availability of potential micro hydropower. The proposed technique is general in nature and could be utilized to assess micro hydropower resources in any region.
Keywords: hydropower; micro